Pendekatan Prinsip Desain Norman Foster pada Perancangan Hotel Bintang 5 di Kota Medan - Ramadhan, Zidhan; Budiani, Ina Triesna (Universitas Medan Area, 2025)
Medan City, known as the gateway for tourists heading to North Sumatra, is currently experiencing rapid development that attracts the interest of many people and investors, both for tourism and business purposes. Besides serving as temporary accommodation for tourists, hotels also play an essential role as facilities for commercial business meetings, offering services and accommodations. When designing a hotel, two crucial aspects must be considered efficiency and comfort. The design process involves specific methods that assist designers in developing their ideas. For the design of a hotel building in Medan City with a Norman Foster architectural approach, a descriptive analysis method is used. This method involves the exposition of natural phenomena and surrounding issues. Descriptive analysis aims to depict and explain phenomena without intervention. This process includes the collection, organization, and presentation of data in a narrative or descriptive manner.